THE EFFECT OF HEALTH EDUCATION ON PERSONAL HYGIENE BEHAVIOUR IN PREVENTING VAGINAL DISCHARGE - Mardelia Astriani; Lia Dian Ayuningrum; Aristy Rian Avinda Putri (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background:As 75% of women experience vaginal discharge once in their life phase and as many as 45% experiences recurring conditions. Lack of knowledge about personal hygiene especially vaginal hygiene is the main cause of vaginal discharge. Aims: The purpose of this research is to find the effect of health education about personal hygiene to a behavior of preventing vaginal discharge. Methods:The study employed a Quasi Experiment with Nonequivalent Control Group Design. Sampling technique by Probability Sampling with Cluster Sampling. A sample of 136 from 206 students were involved anddivided into two groups; control and experimental group. The instrument used was questionnaire related to vaginal hygiene.Independent-t tests were used to analyze data to differences between experimental and control groups. And then paired t-test is used to see the difference betweenpretest and postest of each group.. Results:From the results, Lavene's test has the same or homogeneous variation with a score of sig 0.771 (sig> 0.05). Then p-value of t-test test obtained sig. 0.000 (sig> 0.05), which indicates a significant difference between groups treated with health education about personal hygiene behavior to preventing vaginal discharge with untreated groups. Conclusion: The conclusion is there was an effect of health education on personal hygiene to student's behavior of preventing vaginal discharge in Wikarya Karanganyar Vocational High School.